2010
DOI: 10.1111/j.1439-0310.2010.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Virtual Parrots’ Confirm Mating Preferences of Female Budgerigars

Abstract: Parrots comprise one of the several taxa in which life‐long learning of new vocal signals used in intraspecific communication is known to occur routinely. The functions and evolutionary bases of this ability are largely unknown. In the budgerigar (Melopsittacus undulatus), males typically imitate their partner’s contact call type during pair formation. However, a female’s initial choice among unfamiliar males is not based on their production of her call type, because birds without prior social contact rarely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Although both sexes can imitate the calls of other individuals, females do so more slowly, and when in male–female pairs, the males imitate the females’ calls (Hile et al 2000; Hile and Striedter 2000). Support for a sexual selection and/or pair-bonding function has been supported in male–female studies (Hile et al 2000; Hile et al 2005; Moravec et al 2006; Moravec and Striedter 2010), but since call sharing also occurs between same-sex individuals, it is likely that imitation serves additional functions beyond promotion of the pair bond. Our work supports the hypothesis that call matching may serve different function(s) depending on the social relationships between the individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although both sexes can imitate the calls of other individuals, females do so more slowly, and when in male–female pairs, the males imitate the females’ calls (Hile et al 2000; Hile and Striedter 2000). Support for a sexual selection and/or pair-bonding function has been supported in male–female studies (Hile et al 2000; Hile et al 2005; Moravec et al 2006; Moravec and Striedter 2010), but since call sharing also occurs between same-sex individuals, it is likely that imitation serves additional functions beyond promotion of the pair bond. Our work supports the hypothesis that call matching may serve different function(s) depending on the social relationships between the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Other hypotheses have been proposed for call sharing including the mate attraction and pair-bonding (Hile et al 2000; Moravec et al 2006; Keenan and Benkman 2008; Sewall 2009; Moravec and Striedter 2010) and group cohesion (Brown 1985; Bradbury et al 2001; Yurk et al 2002) hypotheses. The mate attraction and pair-bonding hypothesis is specific to mated pairs and suggests that the process of convergence or imitation can have two effects on pair bond formation: (1) it may help reinforce social bonds, and (2) it may enhance individual recognition of one's mate (Hile et al 2000; Moravec et al 2006; Keenan and Benkman 2008; Sewall 2009; Moravec and Striedter 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike chimpanzees or wolves, however, in which observing unfamiliar conspecifics may elicit hostility and familiarity biases for contagious yawning have been reported (Campbell and de Waal 2011;Romero et al 2014), budgerigars show more fluid flocking and thus we did not expect a strong bias for contagious yawning. Since previous research has demonstrated that budgerigars respond to video displays of real and virtual conspecifics (Mui et al 2008;Moravec et al 2010;Mottley and Heyes 2003), Study 2 compared the yawn frequency of the same birds from Study 1 during exposure to video presentations of yawns versus control behaviors.…”
Section: Introductionmentioning
confidence: 99%